DESSECAÇÃO ANTECIPADA EM CANOLA E SEUS EFEITOS SOBRE PERCENTUAL DE GRÃOS COM ÓLEO - VALENTINI, ANA P. F.; PARAGINSKI, ANTONIO A.; ZAMBONATO, FELIPE; GAVIRAGHI, FERNANDO; WÜNSCH, JAIME A.; MARTINS, JOÃO A. K.; SILVA, JOSÉ A. G. D.; WAGNER, JULIANO F.; MOTTA, MARCELO; CIOTTI, RODRIGO (Salão do Conhecimento, 2013)
Resumo